Pensamiento vivo de José Cecilio del Valle - Valle, Rafael Heliodoro (San José : EDUCA, 1971)
+
Otras ediciones: 3a ed. 1982 en CEDIF.
Keywords: VALLE, JOSE CECILIO DEL, 1780-1834; BIOGRAFIAS; AMERICA CENTRAL; HISTORIA